IMPLEMENTATION OF VILLAGE REGULATIONS FROM A CONSTITUTIONAL LAW PERSPECTIVE - Anwar Hidayat (Jurnal Scientia, 2022)
This research aims to investigate the implementation of village regulations in the context of constitutional law. By focusing on a constitutional law perspective, this research analyzes how regulations issued by villages are implemented within a larger legal framework. This research is normative legal research based on related legal rules. The research results show that Law Number 6 of 2014 concerning Villages, supported by implementing regulations and related regulations, creates a comprehensive legal framework for village management and development in Indonesia. Although village regulations have a complex position, as legal and political products, close supervision by local government ensures that village regulations meet legal standards and the needs of local communities. Through a legislative process that involves community participation and coordination between regional and village governments, it is hoped that quality village regulations will be realized and provide legal certainty and prosperity for village communities.